CO2 electroreduction at AuxCu1-x obtained by pulsed laser deposition in O2 atmosphere. (20th August 2017) - Roy, C.; Galipaud, J.; Fréchette-Viens, L.; Garbarino, S.; Qiao, J.; Guay, D.
Graphical abstract: Abstract: Aux Cu1-x thin films were synthesized by pulsed laser deposition (PLD) and their electrocatalytic properties towards CO2 reduction in aqueous solution were assessed. The presence of an O2 atmosphere during the PLD process modified the chemical nature of the resulting Aux Cu1-x films, with different oxide types identified by X-ray photoelectron spectroscopy. The impact of these oxides, and of the Cu/Au stoichiometry, on the partial current density and conversion efficiency were assessed. The formation of Aux Cu1-x alloy thin films and/or the introduction of an O2 atmosphere during deposition does not yield to any marked increase of the formation of carbonaceous compounds, and CO and H2 were the only two products formed, along with formate detected in trace amounts ( < 1%). Oxide-derived Au catalysts obtained by PLD under O2 atmosphere do not alter CO2 selectivity towards CO formation. High copper content catalysts deposited in vacuum exhibit the lowest overall CO FE%, while increasing the Au content enhances it. The same trend is observed for Aux Cu1-x catalysts deposited under 2 and 220 mTorr O2, aside from the fact that increasing Cu content under high O2 pressure has a less negative influence on CO FE%.